ANALISIS PENDAPATAN PETERNAK SAPI POTONG SKALA RENDAH DI DESA ALATENGAE KECAMATAN BANTIMURUNG KABUPATEN MAROS - Aisyah, Aisyah; Sirwan, A. Muh. (JURNAL LENTERA AKUNTANSI, 2023)
The cattle farming enterprise in Alatengae Village, Bantimurung District, Maros Regency, is a community initiative aimed at enhancing income sources. This research aims to identify the income of livestock farmers with a herd size ranging from 1 to 5 head of cattle in Alatengae Village, Bantimurung District, Maros Regency. The study was conducted between February and April 2021 at the specified location. A sample of 31 respondents was selected for the study. The data utilized in this research were of a quantitative nature, and data analysis was performed using income analysis formulas. The research findings indicate that the cattle farming enterprise in Alatengae Village, Bantimurung District, Maros Regency, whether in breeding or fattening systems, exhibited an R/C (Revenue to Cost) ratio greater than one. Therefore, from an economic feasibility perspective, the cattle farming enterprise in Alatengae Village, Bantimurung District, Maros Regency, generates profits and has the potential for sustainable development.Key words: Income Analysis, Small-Scale Beef Cattle Farming